QURAN INTERPRETATION AND SOCIAL CHANGE: IMPLICATIONS FOR RELIGIOUS PRACTICES IN THE MODERN ERA - Syahroni Siahaan; Mhd. Khaidir Ali (STAI Sebelas April Sumedang, 2023)
Abstract This study explores the dynamic interaction between Qur'anic exegesis (tafsir) and social change, focusing on how traditional and contemporary interpretations of the Qur'an influence modern Islamic practices. Utilizing a qualitative approach, the research analyzes primary sources, including classical tafsir such as Tafsir al-Jalalain and Tafsir al-Tabari, and contemporary works like Tafsir al-Mishbah by Quraish Shihab. The study employs hermeneutic text analysis to examine how these interpretations address issues such as gender equality, human rights, and modernization. Findings indicate that while traditional tafsir remains central in conservative communities, its limitations in addressing contemporary issues are evident. Conversely, progressive tafsir offers more adaptive interpretations that resonate with urban and educated Muslim populations. This divergence reflects the broader tension between tradition and modernity in Islamic thought. The study contributes to the ongoing discourse on how Islamic teachings can evolve to meet the needs of a changing world while maintaining their core values.